Assessing the Similarity of Injunctive Norm Profiles Across Different Social Roles: The Effect of Closeness and Status in the United States and China. (November 2019) - Buchtel, Emma E.; Ma, Paolo P. L.; Guan, Yanjun
Do social roles affect injunctive norms for behavior and more so in Chinese than American cultural contexts? We use mixed methods to analyze open-ended data describing appropriate behavior within social roles that differ in interpersonal closeness and relative status. American ( N = 401) and Chinese ( N = 392) participants provided descriptions of ideal behavior of two actors in one of 16 role dyads. The 2, 219 (American) and 1, 466 (Chinese) behavior descriptions were coded into 71 content categories, forming profiles of appropriate behavior for six social roles (Close/Distant × Low/Equal/High status). First, we adapt a method for assessing profile similarity in personality psychology to quantitatively evaluate how closeness and status affect similarity between the six social roles. By separating profiles into normative (average behavior) and distinctive (behavior specific to a particular social role) components, we find that distinctive behavioral profiles for specific social roles vary systematically by closeness/status in both American and Chinese data; we also find a larger effect of closeness in Chinese data. Second, we qualitatively analyze the content of the distinctive behavioral profiles through the lens of the rapport management model, showing how rights and obligations associated with each role vary, and finding cultural differences in which behaviors appropriately manage these expectations. Quantitative findings emphasize the cross-cultural importance of interpersonal situations for determining appropriate behavior, with some evidence for a greater effect in Chinese culture; qualitative results reveal the culturally specific ways in which relational situations direct expectations for behavior.